Black-Box Modelling For Brushless Dc Motor And Control Strategy For Quadcopter Applications - Nor, Muhammad Haziq Mohamed (Universiti Sains Malaysia, 2021)
The uses of brushless DC motor in quad copter application gives rise to a new demand. Quad copter drone usually uses brushless DC motor due to high performance, high efficiency and small volume. The function of brushless DC motor in quad copter is for positioning and velocity of the drone itself. Surely brushless DC motor gives more efficiency and effectiveness compared to brush motor. In order to analyse the responses of the brushless DC motor and control strategy for quad copter applications, black box modelling is invent. Black box or known as experimental modelling is a method for the development of process database of the models. Since physical simulation cost so much times, black box modelling is a common way to gain the overall behaviour process input and output. Typically, the built model used for estimation of potential process values or in application for process management. Important aspects in black box modelling which is system analysis, data conditioning, key variable analysis, model structure design, model identification and model evaluation. Software that been used is MATLAB and Simulink. The MATLAB and Simulink software used to demonstrate and measure the effective performance of the concept. The software helps in designing and identification of the system of the quad copter. Usually, the performances of different linearity of the models give different results of the models. Surely, linear transfer function models gives the best result for the simulation.